Five new species of Acanthobothrium (Cestoda: Onchoproteocephalidea) from the long-tailed butterfly ray, Gymnura cf. poecilura (Elasmobranchii: Gymnuridae), from the Persian Gulf and Gulf of Oman - Maleki, Loghman; Malek, Masoumeh; Palm, Harry W. (Zootaxa, 2019)
Five new species of Acanthobothrium Blanchard, 1848 are described from Gymnura cf. poecilura from the Gulf of Oman and Persian Gulf. They all belong to the Category 1 and can be differentiated from all congeners by a combination of characters, including marginal lappets on the bothridial rim, the lack of spinitrich microtriches on the proximal bothridial surfaces, the position of the genital pore in the posterior one fifth of the proglottid, the direction of the cirrus sac parallel and clinging to the ovarian lobe, the lack of post-vaginal testes, and the interruption of the vitelline follicles by the ovary. The five new species are morphologically similar to each other but differ among each other in their cephalic peduncle length, proglottid and testes number, and the apolysis status. The most similar species to this new group is Acanthobothrium fogeli Gloldstein, 1964 from the Gulf of Mexico. The new species differ from A. fogeli by the muscular pad size, cephalic peduncle length and having marginal lappets on the bothridial rim. the species of Acanthobothrium occurs in three families of elasmobranchs in the Gulf of Oman and Persian Gulf (Dasyatidae, Rhynchobatidae and Gymnuridae). The true identity of many hosts in the region is ambiguous. Therefore, we designated the sampled elasmobranch as G cf. poecilura in accordance to the previously molecular study on a few individuals from the region.